Formula Optimization of the Oral Liquid with Lycium barbarum Leaves Flavonoids and Its Effect on Improving the Antioxidant Activity in Aging Mice - Jiangxue QIN; Xue YANG; Jinwang LIU; Jing FU; Yanli FAN (Shipin gongye ke-ji)
In this study, Lycium barbarum leaves flavonoids (LBLF) were used as the main raw material, and the formula of LBLF oral liquid was optimized through single-factor and response surface experiments, and the in vivo antioxidant activity of the oral liquid was evaluated by aging model mice. The results showed that the optimum formula of the LBLF oral liquid was as follows: The concentration of LBLF was 8 mg/mL, the amount of malic acid was 0.100%, the amount of sucralose was 0.12%, and the amount of the composite stabilizer was 0.15%, and the total flavonoids content in the oral liquid was (8.23±0.52) mg/mL. In addition, the oral liquid could significantly enhance the activities of superoxide dismutase (SOD), catalase (CAT) and reduced glutathione (GSH) in the serum, liver and brain tissues of aging model mice (P<0.05). Meanwhile, it could also prominently decrease the content of malondialdehyde (MDA) (P<0.05). Therefore, it could be concluded that this LBLF oral liquid had a good antioxidant capacity. This study could provide ideas and a solid research foundation for the further processed products development of Lycium barbarum leaves.